Turismo rural no Rio Grande do Sul: perfil, motivações e experiências - Klimeck, Beatriz (2024)
Rural tourism has grown significantly in Brazil, becoming a non-agricultural activity that stimulates local development and can make rural areas more dynamic with different earning possibilities. In this way, rural tourism can provide tourists with a new way of doing tourism, thus seeking to awaken different emotions and feelings. The main objective of this study was to describe tourists' motivations for practicing rural tourism in Rio Grande do Sul – Brazil. The theoretical framework addresses the different existing definitions of tourism in rural areas, it also addresses aspects of its potential for territorial development, as well as the tourist experience that rural tourism provides for tourists. The method used is the Survey, with a qualitative and quantitative approach. Data collection took place through the preparation of a questionnaire with attributes derived from the literature review, in the period of October 2023, which obtained 468 respondents practicing rural tourism. In this way, it was found that rural tourists have different profiles and ages, looking for tourism that is done as a family and with the aim of distancing themselves from mass tourism. They highlight several destinations that can be explored, whether from the most popular in Rio Grande do Sul to the most unknown, carrying out their activities at least once a year and staying for one day or more. As for the practice of the activity, the factors listed are considered egalitarian for the respondents, with rural tourism seen in accordance with past perceptions, nostalgia, local authenticity, experiences and motivations generated in each participant. Finally, it can be noted that the factors that respondents most seek are places that have nature, outdoor activities, local culture, typical cuisine, as well as tranquility.